2019
DOI: 10.1016/j.chiabu.2018.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Developmental timing of polyvictimization: Continuity, change, and association with adverse outcomes in adolescence

Abstract: Children who experience polyvictimization (i.e., exposure to multiple and varied traumatic stressors) are at heightened risk for psychopathology. While polyvictims generally have worse outcomes than those with fewer types of traumatic experiences, not all polyvictims experience significant, or similar, impairment suggesting that polyvictims are a heterogeneous group. This variation in outcomes among polyvictimized children, may be due to differences in how polyvictimization is operationalized and measured. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 43 publications
5
68
0
3
Order By: Relevance
“…() identified two groups predominantly (i.e., 71%–98%) composed of women (i.e., polyvictims with child and adult interpersonal trauma histories as well as adult community trauma survivors) and two groups composed almost exclusively (90%–100%) of men (i.e., community trauma survivors reporting adult traumatic accidents, physical assaults, and combat exposure). Consistent with evidence that polyvictimization across developmental epochs is associated with the most severe and complex symptoms (Dierkhising, Ford, Branson, Grasso, & Lee, ), members of the polyvictimization class were particularly likely to be classified as CPTSD and specifically as DSO. Members of the polyvictimization class were also likely to not have a clear memory of traumatic events they experienced and were more likely than adult community trauma survivors to report past sexual assaults in childhood and/or adulthood.…”
Section: Validity and Trauma Antecedents Of Complex Ptsdsupporting
confidence: 66%
“…() identified two groups predominantly (i.e., 71%–98%) composed of women (i.e., polyvictims with child and adult interpersonal trauma histories as well as adult community trauma survivors) and two groups composed almost exclusively (90%–100%) of men (i.e., community trauma survivors reporting adult traumatic accidents, physical assaults, and combat exposure). Consistent with evidence that polyvictimization across developmental epochs is associated with the most severe and complex symptoms (Dierkhising, Ford, Branson, Grasso, & Lee, ), members of the polyvictimization class were particularly likely to be classified as CPTSD and specifically as DSO. Members of the polyvictimization class were also likely to not have a clear memory of traumatic events they experienced and were more likely than adult community trauma survivors to report past sexual assaults in childhood and/or adulthood.…”
Section: Validity and Trauma Antecedents Of Complex Ptsdsupporting
confidence: 66%
“…Recently, in a study on 1,177 young people with expansive gender and sexual identities, Sterzing and colleagues (2017) found that 39.3% of the adolescents experienced polyvictimization (i.e., 10 or more adverse events) during the past year, nearly twice the prevalence found for youth drawn from the general population (Finkelhor, Ormrod, & Turner, 2007). While this study did not explicitly assess the co-occurrence between maltreatment types, it is likely that many of the cases of polyvictimization involved multiple types of maltreatment, CHILDHOOD MALTREATMENT AND IPV AMONG LESBIAN GAY BISEXUAL INDIVIDUALS 5 based on other studies on polyvictimization in high-risk youth or young adult populations (Charak et al, 2016;Charak, Ford, Modrowski, & Kerig, 2018;Dierkhising, Ford, Branson, Grasso, & Lee, 2018). Together, these studies suggest that the co-occurrence of types of childhood maltreatment is likely among LGB individuals.…”
Section: Childhood Maltreatment Among Lgb Individualsmentioning
confidence: 98%
“…More recently, research has paid more attention to the impact of exposure to multiple victimization types, or "poly-victimization" [25]. Dierkhising, Ford, Branson, Grasso and Lee [26] defined poly-victimization as "exposure to multiple and varied traumatic stressors involving interpersonal violence" (p. 41). It has been found that different forms of victimization are interrelated in such a way that the adolescents who experience one type are also likely to be exposed to other forms of victimization [27].…”
Section: Introductionmentioning
confidence: 99%